A new species of Gegeneophis Peters (Amphibia: Gymnophiona: Caeciliidae) from the surroundings of Mookambika Wildlife Sanctuary, Karnataka, India - Bhatta, Gopalakrishna; Srinivasa, R. (Zootaxa, 2004)
A new species of Indian caecilian, Gegeneophis madhavai (Amphibia: Gymnophiona: Caeciliidae) is described from two specimens collected from the Western Ghats of southern Karnataka. This species is distinguished from all other species of the genus in having visible eyes, fewer than 100 primary annuli and more than 25 secondary annuli confined to the posterior of the body.